Impact of Environmental Factors, Organizational Structure, Conflict Management, and Internal Control on the Effectiveness of Islamic Schools in Banten - Nur Afif; Muhammad Adlan Nawawi; Erna Fauziah (AL-ISHLAH: Jurnal Pendidikan, 2024)
The rapid increase in the number of schools necessitates the evaluation of educational quality across all institutions, including both private and state-run schools, with a particular focus on Islamic schools. Organizational performance serves as a key indicator of an institution's effectiveness. This study aims to analyze the impact of organizational structure, conflict management, and internal control on the work environment and effectiveness of teachers in Islamic schools in Banten. The study population comprised teachers from Islamic schools in Banten, with a total sample size of 58 teachers. Data analysis was conducted using path analysis to assess the relationships between the variables. The analysis revealed that organizational structure, conflict management, and internal control positively influenced the teachers' work environment. Furthermore, the organizational structure was found to have a significant impact on work effectiveness. However, conflict management and internal control did not show a significant effect on teachers' work effectiveness. Additionally, the work environment had a positive effect on the effectiveness of the teachers' work. The findings indicate that a well-defined organizational structure enhances both the work environment and the effectiveness of teachers in Islamic schools. While conflict management and internal control are beneficial for improving the work environment, they do not directly influence work effectiveness. The positive correlation between the work environment and teacher effectiveness underscores the importance of fostering a supportive and well-structured organizational setting. This study underscores the critical role of organizational structure in enhancing teacher effectiveness in Islamic schools. While conflict management and internal control improve the work environment, their direct impact on effectiveness is limited. Creating a conducive work environment remains essential for maximizing the performance of teachers.